1973
DOI: 10.1159/000122153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Restriction on Reproductive Function in Female Rats

Abstract: Reproductive function and sexual behavior were examined in female rats subjected to a restricted watering schedule. In 4- or 5-day cycling rats, water was supplied only from 09.00 to 10.00 h each day for a minimum of 1 month. A tendency towards prolonged estrous cycles was noted, with 5-day cycles predominating, regardless of the pretreatment cyclical pattern. Water-restricted 5-day rats became sexually receptive earlier on the day of proestrus than did controls. Barbiturate was more effective in blocking ovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Smith et al [1973] have also observed a correlation between disturb ances in adrenocortical activity induced by water deprivation in rats and reproductive function. Armstrong and Kennedy [1972] have summarized the recent literature on adrenal-gonadal interactions and fertility and have proposed that the adrenal cortex secretes hormones that can adjust the timing of the ovulatory surge of gonadotrophin during proestrus in the rat.…”
Section: Discussionmentioning
confidence: 83%
“…Smith et al [1973] have also observed a correlation between disturb ances in adrenocortical activity induced by water deprivation in rats and reproductive function. Armstrong and Kennedy [1972] have summarized the recent literature on adrenal-gonadal interactions and fertility and have proposed that the adrenal cortex secretes hormones that can adjust the timing of the ovulatory surge of gonadotrophin during proestrus in the rat.…”
Section: Discussionmentioning
confidence: 83%
“…Al terations in the diurnal rhythm of corticosterone secretion are associated with changes in reproductive cycles in ro dents. Restricting water availability to a short period of time each day resulted in an abnormal rise in plasma corticoste rone just prior to the watering period in female rats [1,15,32], These changes in corticosterone secretion were associat ed with a lengthening of the estrous cycle from 4 to 5 days, increased susceptibility to barbiturate blockade of ovula tion, a tendency toward a more erratic pattern of LH secre tion and a prolongation of the proestrous surge of prolactin …”
mentioning
confidence: 99%